2022
DOI: 10.1101/2022.12.25.521884
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PanCanSurvPlot: A Large-scale Pan-cancer Survival Analysis Web Application

Abstract: The identification of reliable tumor prognostic markers can help clinicians and researchers predict tumor development and patient survival outcomes more accurately, which plays a vital role in clinical diagnosis, treatment effectiveness assessment, and prognostic evaluation. Existing web tools supporting online survival analysis are gradually failing to meet the increasing demands of researchers in terms of the dataset size, richness of survival analysis methods, and diversity of customization features. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In addition, the mRNA and protein levels of CDK5RAP3 were overexpressed in glioblastoma clinical samples compared with normal tissues (Figure 6 D and 6 E) 24 . The overexpression of CDK5RAP3 was corelated with poor overall survival of glioblastoma patients (Figure 6 F) 25 . Furthermore, CDK5RAP3 knockdown successfully reversed the enhanced migrative and invasive abilities induced by TSPAN6 overexpression in glioblastoma cells (Figure 6 G and 6 H, Figure S4 B).…”
Section: Resultsmentioning
confidence: 97%
“…In addition, the mRNA and protein levels of CDK5RAP3 were overexpressed in glioblastoma clinical samples compared with normal tissues (Figure 6 D and 6 E) 24 . The overexpression of CDK5RAP3 was corelated with poor overall survival of glioblastoma patients (Figure 6 F) 25 . Furthermore, CDK5RAP3 knockdown successfully reversed the enhanced migrative and invasive abilities induced by TSPAN6 overexpression in glioblastoma cells (Figure 6 G and 6 H, Figure S4 B).…”
Section: Resultsmentioning
confidence: 97%
“…Similarly, higher clinical stages of bladder cancer also displayed augmented HSPB8 expression (Figure 1 D). To explore the potential impact of HSPB8 on the prognosis of bladder cancer patients, we utilized the PanCanSurvPlot 9 online tool to conduct survival analyses on tissue samples from both TCGA and GEO databases. The findings revealed that patients with high HSPB8 expression in the TCGA database had a significantly lower overall survival rate ( P < 0.05) and disease-specific survival ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…We used the PanCanSurvPlot 16 (https://smuonco.shinyapps.io/PanCanSurvPlot/) to obtain the survival plots of CSF3R in cancer patients, including overall survival (OS) and disease‐specific survival (DSS).…”
Section: Methodsmentioning
confidence: 99%
“…PanCanSurvPlot 16 Survival plots of CSF3R in cancer patients cBioPortal 17,18 Genetic alterations of CSF3R and the survival significance in cancer patients…”
Section: Bioinformatic Tools Functionmentioning
confidence: 99%